Asymmetry of the lower limbs in breaststroke swimming - Czabanski, B. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
This study involving the investigations of the causes of asymmetrical kicks during breaststroke swimming should be of initial value to teachers and coaches. The results will also contribute to the lmowledge in the general area of laterality as it relates to human movement. Although the study is concerned with asymmetry of limb motion in the breaststroke kick, the findings may provide insight into the general problem of asymmetrical motion.